Effect of storage and disinfection methods of extracted bovine teeth on bond strength to dentin - Maria Malerba Colombi Humel; Marcelo Tavares Oliveira; Vanessa Cavalli; Marcelo Giannini (Universidade Estadual de Campinas, 2016)
The aim of this study was to evaluate the effect of storage and disinfection methods (SDM) on bond strength (BS) to bovine dentin, using two adhesive systems: Adper Single Bond and Clearfil Protect Bond. Method: Extracted bovine teeth were assigned to the following SDM: 100% Humidity (HU); Gamma Radiation (GR); Autoclave (AU); 0.10g/mL Thymol (TH); 10% Formalin (FO); Frozen (FR); 0.2% Sodium Azide (SA) and 0.5% Chloramine T (CT) (n=10). The GR and AU groups were submitted to sterilization methods and stored at 100% humidity for 24 hours at 37C°, before testing. TH, FO, FR, SA and CT groups were stored for three months at 5C°, except for FR (-4C°). The adhesive systems were applied according to manufacturer's instructions. For BS testing, the micro-shear test was performed, using Tygon mold (0.75mm diameter and 1mm high), which was filled with Clearfil AP-X (Kuraray) composite resin. Data were analyzed by two-way ANOVA and Tukey Test (p<0.05). BS of adhesive systems was similar for all SDM, except for 10% formalin. HU, GR, AU, TH and SA did not change the BS for the adhesives tested. For most of SDM, BS of adhesive systems was similar. Some 3 month-SDM groups (FR, FO and CT) reduced the BS.